PENGARUH MORALITAS INDIVIDU, ASIMETRI INFORMASI, EFEKTIVITAS PENGENDALIAN INTERNAL DAN KETAATAN ATURAN AKUNTANSI TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI (Studi pada BUMD Provinsi Riau) - Tarigan, Laurensia Br; Hasan, Amir; Silfi, Alfiati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This research was conducted examine the the effect of individual morality,information asymmetry, Effectiveness of Internal Control and compliance to accounting rules on the tendency of accounting fraud in BUMD Riau. Collecting data using guesionnaires. Data of this research obtained from head and staf accounting. Of the 70 guesionnaires distributed, the number of returnees is 66 guesionnaires and a guesionnaire that can be processed a number of 64 guesionnaires. Data were analyzed by using multiple regression (multiple regression) with the help computer program SPPS versi 18.0. The result showed that the Individual Morality,Information Asymmetry, Effectiveness of Internal Control And Compliance To Accounting Rules influence on the fraud tendency of accounting.Keywords:morality, information asymmetry, effectiveness of internal control, compliance to accounting rule and fraud